Purification of a Specific Placental Plasminogen Activator Inhibitor by Monoclonal Antibody and Its Complex Formation with Plasminogen Activator - Åstedt, B; Lecander, Ingegerd; Brodin, T; Lundblad, A; Löw, Karin (Thrombosis and Haemostasis, 1985)
A monoclonal antibody of IgG2a-type was obtained against a specific fast acting plasminogen activator inhibitor found in placenta. The placental inhibitor was purified by affinity chromatography using the monoclonal antibody and additionally in a FPLC-system. A strong complex formation was found between the inhibitor and urokinase and also with the two-chain form of plasminogen activator of the tissue-type. A weaker complex was found between the placental inhibitor and the one- chain form of the tissue-type activator.
Keywords: Monoclonal antibody; Plasminogen activator; Coagulation tests; Urokinase; Placental inhibitor